Creative deviance and respect for authority: A case study of selected auditing and accounting firms in Ghana. - AKOUBILA, ALBERT NYAABA (KNUST, 2025)
A Thesis Submitted To The Department Of Human Resource And Organisational Development (HROD, In Partial Fulfilment Of The Requirement For A Degree Of MASTER OF BUSINESS ADMINISTRATION (Management And Organisational Development).